2019
DOI: 10.1177/2048872619882424
|View full text |Cite
|
Sign up to set email alerts
|

HEART score improves efficiency of coronary computed tomography angiography in patients suspected of acute coronary syndrome in the emergency department

Abstract: Aims: Coronary computed tomography angiography is increasingly employed in the emergency department for suspected acute coronary syndrome patients. The HEART score has been proposed for initial risk stratification in these patients. The aim of this study was to investigate the diagnostic value and efficiency of the HEART score before coronary computed tomography angiography. Methods and results: We included patients suspected of acute coronary syndrome who underwent coronary computed tomography angiography in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In recent years, with the changes of social environment and living habits, the incidence of coronary heart disease is also getting higher and higher. It has been called one of the main causes of human death in cardiovascular diseases, which poses a serious threat to human life and health (1,2). The gold standard for the diagnosis of coronary heart disease has been coronary angiography, which has high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the changes of social environment and living habits, the incidence of coronary heart disease is also getting higher and higher. It has been called one of the main causes of human death in cardiovascular diseases, which poses a serious threat to human life and health (1,2). The gold standard for the diagnosis of coronary heart disease has been coronary angiography, which has high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Arslan et al reclassified 74.1% of patients with intermediate HEART scores as low risk using CCTA. 20 Shin et al similarly reclassified 68.7% as low risk, 28.7% more than the HEART Pathway alone. 21 Our collective findings are important given that that only 36% of US hospitals staff dedicated observation units according to the latest National Hospital Ambulatory Medical Care Survey.…”
Section: Discussionmentioning
confidence: 99%
“…Also, those studies assessed HEART scores only in patients who underwent CCTA, excluding a significant proportion of low-risk patients. 20,21 Our study included all low-risk patients, which more closely aligns with real-world scenarios in which ED providers will use the HEAR score to determine whether CCTA is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The HEART score (HS) is designed for acute risk stratification of CP in the emergency setting to identify low-risk patients eligible for discharge without further testing and has been validated for safety and efficacy. 13 Arslan et al 14 performed a secondary analysis of ED patients with ACS symptoms undergoing CCTA and found that combining HS with CCTA significantly and safely reduced the need for CCTA.…”
Section: Importancementioning
confidence: 99%